TikTok Social Media Platform in Influencing Political Participation in Novice Voters at Christian Private High School 2 Medan: Platform Media Sosial TikTok dalam Mempengaruhi Partisipasi Politik pada Pemilih Pemula di SMA Swasta Nasrani 2 Medan - fatimahazzahra; Hizkia Roland Prwyra Sitorus; Jacklyn Alona Br. Bangun; Triya Anggraini; Bayu Ardian Syahputra; Desriani Ronay Fiona Purba (Universitas Veteran Bangun Nusantara, 2025)
Technological developments are growing very rapidly, especially in social media information technology. Social media users are also very busy, especially the Tiktok application. This social media has been widely used by generation Z and also political parties. Several political parties use the Tiktok application to conduct political campaigns. This research was carried out to see the influence of the Tiktok application on the political participation of beginner voters. This type of research is quantitative observational which was carried out at the Private Christian High School 2 Medan. The sample size is 30 teenagers or beginner voters in class XII in 1 class for the 2024/2025 academic year. This research found that 53% of respondents strongly agreed with using the TikTok social media platform to get information about political issues. TikTok plays an active role in influencing political participation among first-time voters. The percentage diagram results show that 50% of respondents voted that the social media platform TikTok was very effective in influencing their political participation in the 2024 election. Keywords: Political Information, Digital Literacy, Political Participation, New Voters, TikTok Platform.